Microstructural heterogeneity induced by thermal accumulation in a nickel–aluminum–bronze alloy additively manufactured via directed energy deposition - Li, Boyuan (2023)
Complex thermal history in directed energy deposition (DED) may induce microstructural heterogeneity and cause early failure of printed parts. This work investigated the effect of thermal history on the microstructure and mechanical properties of a DED-printed nickel–aluminum–bronze part for the first time. The printed part exhibited significant heterogeneity in the microstructure and tensile properties at its top, middle, and bottom locations. The microstructure at the top and middle locations consisted of a coarse α phase, while the bottom location possessed the Widmanstätten α phase embedded in the β' matrix. The highest mechanical strengths were achieved at the bottom location.